Spatiotemporal Modeling - Churnside Harrison, Róger (2008)
From a theoretical and logical perspective organizations are shown to involve a quantity of work that is not the simple sum of individual labor, but a multiplication or fraction of that sum determined by the ratio of operative time to management time. This ratio has a dual character: it is derived from the structure of organizations; but it also reacts upon that structure. In practical terms, the model provides measurements of organizational phenomena such as mutual responsability or commitment between managers and laborers; which, in economic and sociological tradition, has only been described implicitly, qualitatively and intuitively . It also allows to describe current processes and problems of stability/instability and growth/decline of organizations, mainly capitalist corporations. The composition of the model, its consequences and predictions are preliminarily illustrated with information from data bases of Booz, Allen and Hamilton, Challenger, Gray and Christmas Inc., and the Economist magazine.